Soft TCPTP Agonism—Novel Target to Rescue Airway Epithelial Integrity by Exogenous Spermidine - Ghisalberti, Carlo A.; Borzì, Rosa M.; Cetrullo, Silvia; Flamigni, Flavio; Cairo, Gaetano (Frontiers in Pharmacology, 2016)
A reparative approach of disrupted epithelium in obstructive airway diseases, namely asthma and chronic obstructive pulmonary disease (COPD), may afford protection and long-lasting results compared to conventional therapies, e.g. corticosteroids or immunosuppressant drugs. Here we propose the polyamine spermidine as a novel therapeutic agent in airways diseases, based on a recently identified mode of action: T-cell protein tyrosine phosphatase (TCPTP) agonism. It may include and surpass single-inhibitors of stress and secondary growth factor pathway signaling, i.e. the new medicinal chemistry in lung diseases. Enhanced polyamine biosynthesis has been charged with aggravating prognosis by competing for L-arginine at detriment of nitric oxide (NO) synthesis with bronchoconstrictive effects. Although excess spermine, a higher polyamine, is harmful to airways physiology, spermidine can pivot the cell homeostasis during stress conditions by the activation of TCPTP. In fact, the dephosphorylating activity of TCPTP inhibits the signaling cascade that leads to the expression of genes involved in detachment and epithelial-to-mesenchymal transition (EMT), and increases the expression of adhesion and tight junction proteins, thereby enhancing the barrier functionality in inflammation-prone tissues. Moreover, a further beneficial effect of spermidine may derive from its ability to promote autophagy, possibly in a TCPTP-dependent way. Since doses of spermidine in the μM range are sufficient to activate TCPTP, low amounts of spermidine administered in sustained release modality may provide an optimal pharmacologic profile for the treatment of obstructive airway diseases